RAISING THE EFFICIENCY OF AGRICULTURAL LAND USE OF VIETNAM ON THE BASIS OF ATTRACTING FOREIGN DIRECT INVESTMENTS - T. T. Vu (Вестник университета)
The issue of attracting FDI investments in Vietnam’s agriculture have been studied. The state of attracting FDI in the Association of south east asian nations countries and in Vietnam for the development of agriculture has been presented. The current serious difficulties and limitations of sources FDI for raising the efficiency of agricultural land use in Vietnam have been assessed. Based on this the solutions that contribute to improving the efficiency of agricultural land use on the basis of attracting FDI into Vietnam’s agricultural sector have been offered.